(3GdehLRs - (3YdGA GdOjf, Ydj Hf CHi GdMRe GdbQTi , GHf GdfajSs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3GdeOjfI s)
(3ChdgG (B:s
(3bGd GdTjN CHh GdMSf YdGA GdOjf Hf (B[ (3CHi(B] (3GdMRe GdbQTi , GdeYQha HGHf GdfajS GdeJWHH, HYO MeO Gddg YR hLd s
(3BNQgG (B:s
(3hef YGa CcdgG eGJ , hcGf JOHjQge hGMO , hGSJYedhG OhGA LGdjfhS hZjQg ef GdYdGL GdePchQ s
(3CLhO eNJUQGJ bGfhf GdTjN GdQFjS GHf SjfGs
(3QJHg Ydi CQHYI afhf YdjgG ghGeT hJYdjbGJs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs